TEACHERS' AND LEARNERS' PERCEPTIONS OF FORMATIVE ASSESSMENT PRACTICE IN ENHANCING LEARNING IN EFL COURSES - Ravy Nhor; Sina Pang; Sereyrath Em (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Assessment is inevitable in education. Formative assessment plays a crucial role in enhancing students' learning and performance. With the growing understanding of the role of formative assessment, many countries in the world have considered formative assessment as the primary mechanism of assessment reform in education. In Cambodia, a shift in focus to formative assessment as its assessment reform aimed at enhancing students has been noticed. The present study employed a quantitative method to examine teachers' and learners' perceptions of formative assessment practices in enhancing learning in Cambodian EFL courses. The participants of this study were 30 teachers (3 females) and 50 students ( 22 males). They are teaching and learning English as a Foreign Language. The results revealed that the respondents have a more positive perception of formative assessment. It highlighted a better understanding of formative assessment concepts, purposes, and development strategies. The results also indicated that participants' perceptions about formative assessment enhance learning in EFL courses through various roles of feedback. The results showed that respondents perceived that it is demanded of assessors or teachers to have higher knowledge about formative assessment to assess students in formative ways. Time-consuming was also perceived as a challenge in formative assessment practice. The findings also revealed that participants were more likely to use formative assessment in their EFL courses in the future. Future studies with many participants, mixed method approaches, and cross-disciplinary research in Cambodia should be conducted in either private or public HEIs.